Edukasi dan Pelatihan Investasi Keuangan Untuk Pelajar Sebagai Investor Pemula di SMK Al-Ihsan Jakarta Barat - Angela Dirman; Annisa Hakim; Erna Setiany (Universitas Negeri Gorontalo, 2022)
There are still many people, especially teenagers who have not realized the importance of having financial management in their personal lives. Now is the right moment for students to start learning to invest. Al-Ihsan Vocational High School West Jakarta is one of the Vocational Schools in the City of Jakarta. As one of the vocational high schools in the city of Jakarta, Al-Ihsan Jakarta Vocational School has the same role as other vocational schools, namely to prepare students to be competent in the chosen field of study. Almost all students at the Al-Ihsan Vocational School in West Jakarta do not understand comprehensively about financial investment, especially mutual fund investment through online. This is what encourages the provision of financial investment education and training. The training is carried out in community service activities in the form of education and training. Financial investment education and training can provide benefits for Al-Ihsan Vocational School students in increasing knowledge and understanding in investing, especially as novice investors with limited funds. Overall, the trainees understood the material presented and were able to try out mutual fund investment applications. The atmosphere of the activity was very conducive and participants were actively discussing. Participants stated that they were very satisfied with the activities held and hoped that similar activities would be held again with different themes.